Occurrence of Postpericardiotomy Syndrome: Association With Operation Type and Postoperative Mortality After Open-Heart Operations - Joonas Lehto; Tuomas Kiviniemi; Jarmo Gunn; Juhani Airaksinen; Päivi Rautava; Ville Kytö (My University, 2022)
Background
Postpericardiotomy syndrome (PPS) is a common complication after cardiac surgery. However, large‐scale epidemiological studies about the effect of procedure type on the occurrence of PPS and mortality of patients with PPS have not yet been performed.
Methods and Results
We studied the association of PPS occurrence with operation type and postoperative mortality in a nationwide follow‐up analysis of 28 761 consecutive patients entering coronary artery bypass grafting, aortic valve replacement, mitral valve replacement, or ascending aortic surgery. Only PPS episodes severe enough to result in hospital admission or to contribute as a cause of death were included. Data were collected from mandatory Finnish national registries between 2005 and 2014. Of all the patients included, 493 developed PPS during the study period. The occurrence of PPS was significantly higher after aortic valve replacement (hazard ratio, 1.97; 95% confidence interval, 1.58–2.46; P<0.001), mitral valve replacement (hazard ratio, 1.62; 95% confidence interval, 1.22–2.15; P<0.001), and aortic surgery (hazard ratio, 3.06; 95% confidence interval, 2.24–4.16; P<0.001), when compared with coronary artery bypass grafting in both univariable and multivariable analyses. The occurrence of PPS decreased significantly with aging (P<0.001). The occurrence of PPS was associated with an increased risk of mortality within the first year after the surgery (adjusted hazard ratio, 1.78; 95% confidence interval, 1.12–2.81; P=0.014).
Conclusions
The occurrence of PPS was higher after aortic valve replacement, mitral valve replacement, and aortic surgery when compared with the coronary artery bypass grafting procedure. Aging decreased the risk of PPS. The development of PPS was associated with higher mortality within the first year after cardiac or ascending aortic surgery.